If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 4(0 + -3x) = 0 Remove the zero: X + 4(-3x) = 0 Remove parenthesis around (-3x) X + 4 * -3x = 0 Multiply 4 * -3 X + -12x = 0 Solving X + -12x = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '12x' to each side of the equation. X + -12x + 12x = 0 + 12x Combine like terms: -12x + 12x = 0 X + 0 = 0 + 12x X = 0 + 12x Remove the zero: X = 12x Simplifying X = 12x
| (7v-6)(4v+7)=0 | | 2l=p+2w | | cos(4x)=-2.5 | | 7d+d+2d+4=5d | | 460=20n+100 | | 4(3x+1)-7x=6+3x+2 | | (P-8)(p-2)=0 | | 4(3c-7)+3(5c+7)=56 | | 5c+5=15 | | (d^4+4d^3+8d^2+4d+4)y=0 | | -4x=16-4x | | -7x-(-6)=8 | | 14=-8k+-3+1 | | (-9)-4m^0= | | X^2-25x+10=0 | | (x-2)(x^2-6x+8)= | | 2x+1s=70 | | 5d-3e=5 | | -0.6+0.05a=5.3 | | 3x-13=4x+7 | | 1+cosx=0.28 | | 0.7x-0.5=0.8x+0.8 | | x^4-10500x^2+1250000=0 | | 3f(x)=(3x^2+10x-8) | | -2x-38=-6(-3-5x)+8 | | 3x^2+5x-2=12 | | 5x^2-20x-20=0 | | y+(x*x)=5 | | 8x-28=-2x+12 | | 5x^2-20-20=0 | | y=h*h | | =(x-1)(x^2+5x-6) |